Associations Between Dietary Antioxidant Intake and Markers of Atherosclerosis in Middle–Aged Women From North-Western Algeria - Diaf, Mustapha; Khaled, Meghit Boumediene (Frontiers in Nutrition, 2018)
Background: The role of several dietary antioxidants in preventing the development and the progression of atherosclerosis has recently aroused considerable interest. Although they are not yet conclusive, most of the existing suggestions support this hypothesis. Objective: The aim of the present work was to investigate the intake of dietary antioxidant nutrients in relation to atherogenic indices in a group of Algerian middle aged women with and without type 2 diabetes. Methods: A cross-sectional study was conducted on a group of middle-aged women from the north western region of Algeria. Anthropometric and biochemical parameters were measured. Dietary intake was assessed using a validated 3-days food record. Atherogenic indices -total cholesterol-to-high-density lipoprotein cholesterol ratio (TC/HDL) and apolipoprotein (apo) B-to-apo A1 ratio, were calculated. Associations between antioxidants dietary intake and atherogenic indices were examined using logistic regressions. Results: 95 women with type 2 diabetes were compared to 93 non-diabetic ones. Statistical differences (p<0.05) were revealed for body weight, height, body mass index (BMI), glycosylated haemoglobin (HbA1c) and total cholesterol levels. Furthermore, significant differences were noted for vitamin C, E and copper dietary intakes. The TC/HDL ratio was significantly associated to the highest quartiles of vitamin C in all patients; 3.519[2.405-4.408], p=0.009 and in non-diabetic women; 3.984[1.775-7.412], p=0.020, respectively. The odd ratios of vitamin E intakes were about 2.425[2.017-5.715], p=0.012 in all patients and 1.843[1.877-2.731], p=0.019 in non-diabetic group, respectively. However, the Apo B/Apo A1 ratio was more correlated to the highest quartiles of zinc and copper in non-diabetic group; OR= 0.059[0.006-0.572], p=0.015 and 0.192[0.048-0.766], p=0.019, respectively. Conclusion: The estimated risk of atherosclerosis measured through the TC/HDL ratio was correlated to vitamins antioxidant intake, while the probable risk assessed by the Apo B/Apo A1 ratio was more associated to the mineral profile.